Correction: Corrigendum: Glycan complexity dictates microbial resource allocation in the large intestine - Artur Rogowski (Nature Portfolio, 2016)
Nature Communications 6 Article number: 7481 (2015); Published 26 June 2015; Updated 5 February 2016 The financial support for the work described in this Article was not fully acknowledged. The Acknowledgements should have included the following: This work was supported in part by a grant to H.J.G.,B.